Characterization, occurrence and natural attenuation of spilled light synthetic crude oil in a boreal freshwater ecosystem. (1st February 2021) - Yang, Zeyu; Shah, Keval; Fieldhouse, Ben; Mirnaghi, Fatemeh; Hollebone, Bruce P.; Lambert, Patrick; Goldthorp, Michael; Brown, Carl E.; Yang, Chun
Graphical abstract: Highlights: The SCO source oil was a conventional light oil. Major oil loss was evaporation immediately following the incident. Oil level decreased for sites away from the incident site after 20-month. Slightly and heavily weathered SCO were detected after 20-month spill. Microbial degradation was the major chemical weathering process after 20-month spill. Abstract: The characterization, occurrence, fate and behaviour of spilled oil in the affected boreal freshwater ecosystem were investigated in this study following a spill in March 2015, in Gogama, Ontario, Canada. A physicochemical property analysis of the source oil showed that the spilled oil was consistent with a conventional light oil. Oil samples collected immediately following the spill had lost their relatively light molecular alkanes and polycyclic aromatic hydrocarbons (PAHs) due to evaporation or dissolution. Twenty months post-spill, oil contamination levels decreased at sites located furthest from the accident site. Most of the sampling sites close to the incident site contained lightly weathered source oil, while some sediment contained heavily weathered source oil. Biogenic and pyrogenic inputs were also present in all the oil-contaminated sediments, where light molecular weight hydrocarbons had higher loss rates than heavy ones. Branched alkanes were more resistant to loss than corresponding straight isomers. Water samples usually had a lower loss of both alkylated PAHs and alkanes than in the underlying sediments. This difference can be ascribed to the fractionation of petroleum hydrocarbons between being deposited in sediment, and being released into water phases, especially when oils were freshly released into the water phase by disturbing bottom sediment. Aside from the rapid loss through evaporation and dissolution, microbial degradation was the major weathering process causing the loss of hydrocarbons 20 months after the spill.